Oral mucosal lesions associated with fixed orthodontic appliances: A review - Kawono, Kawono; Chuan, How Kim; Halim, Susanna (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Orthodontic procedures enhance dental well-being, yet they can lead to painful sores due to irritation from devices. These sores, often found on the inner cheeks and lips, arise from friction caused by brackets, wires, and screws, resulting in discomfort and slow recovery. To prevent these issues, one can use orthodontic wax, materials that are friendly to the body, and make adjustments to the appliances. Innovative treatments like low-level laser therapy and personalized 3D-printed devices are proving to be promising options for relief. Regular check-ups and working together as a team are essential for providing effective care. Addressing issues early can lessen complications, boost comfort, and improve results of orthodontic care, emphasizing the importance of both preventive and treatment methods in practice.